Impact of hybrid seeds on demand for labour: the case of chilli production in Indonesia. Issue 5 (1st May 2020) - Sayekti, Apri Laila; Zeng, Di; Stringer, Randy
Abstract : Purpose: This paper examines the labour demand associated with hybrid chilli adoption, a relatively labour-intensive crop in Indonesia. Design/production/approach: Using 228 chilli producing households in West Java Province, Indonesia's primary chilli production region, the analysis extends previous research on household labour demand by assessing the impacts of hybrid chilli seed adoption on both family and hired labour on a gender-specific basis. Instrumental variables 2SLS approach is employed to address potential endogeneity that may occur related to hybrid seed choices. Findings: The results demonstrate that hybrid chilli seed use is more likely to increase demand for hired labour, particularly female hired labour; However, hybrid seed adoption is insignificantly associated with demand for male and female family labour. Research limitations/implications: The sample size used in this paper is relatively small; however, the sample is chosen from the biggest chilli producing area in Indonesia and can still be considered reasonably representative. Social implications: The results indicate that hybrid seed adoption creates rural employment opportunities for rural women in Indonesia, which could potentially help empower them in rural economic activities and household decision making. Originality/value: This study contributes to the literature assessing modern agricultural technologies by evaluating rural employment impacts on a source- and gender-specific basis, which is much less understood. It, therefore, complements the existing knowledge regarding welfare impacts in other aspects such as poverty reduction, food security and nutrition enhancement and suggests another dimension where desirable impacts may occur through associated women's empowerment.